A synopsis of the Neotropical genus Protoneura (Odonata: Coenagrionidae) - Ellenrieder, Natalia Von; Garrison, Rosser W. (Zootaxa, 2017)
A synopsis of the Neotropical genus Protoneura is presented, including an identification key to its 22 species accompanied by illustrations of diagnostic characters, and characterizations, diagnoses, and distribution maps for all species. A lectotype is designated for P. peramans Calvert in Skinner, 1902.